Effect of Pasteurella multocida Soluble Antigen Stimulation on the In Vitro Response of Peripheral Blood Mononuclear Cells of Holstein Calves - Ohtsuka Hiromichi (Sciendo, 2018)
The expressions of cytokines mRNA, including interleukin-4 (IL-4), interleukin- 17A (IL-17A) and interferon-gamma (IFN-γ), their master regulatory transcription factors, and signal transducers and activator of transcription (STAT) stimulated in vitro with Pasteurella (P.) multocida soluble antigen were examined in peripheral blood mononuclear cells (PBMC) from Holstein calves. The healthy Holstein calves were divided into three groups; 2 weeks old (2W Group, N=8), 6 weeks old (6W Group, N=8), and 10 weeks old (10W Group, N=8). PBMC were stimulated in vitro by soluble antigen of P. multocida. There were significantly lower expressions of IFN-γ, IL-4, and STAT-6 mRNA of PBMC stimulated with P. multocida soluble antigen in the 2W Group compared to that in the 10W Group. Expression of IL-17A and IFN-γ in PBMC stimulated with P. multocida soluble antigen were significantly higher compared with the PBMC without stimulation in the 6W groups. The results of the present study demonstrated that 2W old calves had decreased cytokine expression of PBMC when in vitro stimulated with P. multocida soluble antigen in vitro.